AB0399 Real-World Experience with Tofacitinib vs Adalimumab (ADA), Etanercept (ETN) and Abatacept (ABA) in Biologic-Experienced Patients with Rheumatoid Arthritis (RA): Data from A US Administrative Claims Database. (15th July 2016) - Harnett, J.; Gerber, R.; Gruben, D.; Koenig, A.; Chen, C.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of RA. Limited real-world data exist comparing tofacitinib with biologic DMARDs (bDMARDs) in biologic-experienced (BE) RA patients (pts). Objectives: To compare pt characteristics, treatment patterns and costs in BE RA pts receiving tofacitinib vs ADA, ETN and ABA using US claims data. Methods: This retrospective cohort study included pts aged ≥18 years with RA (ICD9: 714.0x–714.4x; 714.81) and ≥1 tofacitinib (identified first) or bDMARD claim in the Truven MarketScan® Commercial and Medicare Supplemental healthcare claims database (01/11/2012–31/10/2014). Pts were continuously enrolled for ≥12 months (mos) pre- /post-index and had 1 bDMARD pre-index (due to greater imbalance in number of tofacitinib/bDMARD pts with ≥2 prior bDMARDs). Monotherapy was defined as absence of select conventional synthetic DMARDs within 90 days post-index. Outcomes were treatment persistence (index refills without a 60-day gap after prescription/administration days' supply expiration), adherence (proportion of days covered [PDC]), and 12-mo pre-/post-index RA-related costs. Adjusted analyses were performed using generalized linear models, which included demography, disease status/duration and pre-index therapy variables; 12-mo pre-index costs were included for cost-related dependent variables. Results: 392 tofacitinib, 178 ADA, 118 ETN and 191 ABA pts met selection criteria. 12-mo pre-index bDMARD use was most common for tofacitinib (78%) vs ADA (60%), ETN (49%) and ABA (48%) pts (all p<0.0001). TNFi were the most common prior bDMARDs for tofacitinib (74%), ADA (92%), ETN (86%) and ABA (93%) pts. Pts who received tofacitinib at index had greater RA-related total/pharmacy costs vs ADA, ETN and ABA pts (all p<0.05) and medical costs vs ADA and ETN pts (both p<0.0001) in 12 mos pre-index, and highest percentage of index monotherapy use (53%) vs ADA (48%), ETN (48%) and ABA (41%; p<0.05) pts. The proportion of pts persistent with index therapy was similar for tofacitinib (43%), ADA (38%), ETN (42%) and ABA (44%) pts and remained so in adjusted analyses. Mean (SD) PDC was 0.55 (0.30) for tofacitinib pts vs 0.57 (0.30) for ADA, 0.59 (0.31) for ETN and 0.44 (0.39) for ABA (p=0.0003) pts. In adjusted analyses, ABA use vs tofacitinib was associated with lower mean PDC; increasing age and commercial insurance coverage were associated with higher PDC. Tofacitinib pts had lower post-index RA-related total costs vs ADA and ABA pts, pharmacy costs vs ADA and ETN pts, and medical costs vs ABA pts (all p<0.05) (Figure ). In adjusted analyses, ABA, ETN and ABA use, commercial insurance coverage and number of pre-index rheumatologist visits were associated with higher total RA-related costs; North Central/Southern regions were associated with lower costs. Conclusions: More BE pts started tofacitinib vs ADA, ETN and ABA after recent (prior 12 mos) bDMARD use; BE tofacitinib pts had the highest proportion of monotherapy use. Persistence and adherence were at least similar for tofacitinib and bDMARD pts. Tofacitinib pts had lower adjusted RA-related total costs post-index vs bDMARD pts. Acknowledgement: Study sponsored by Pfizer Inc. Editorial support provided by K Munn of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: J. Harnett Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Gerber Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Koenig Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Chen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc